The Greek origin of caduceum: Æsculapius. - Rillo, Arturo G. (Colombia Medica, 2008)
Introduction: Medicine history gives us the chance to reflect about the Caduceus as the synthesis of the dialectic of the sensible and spiritual life. This opens and horizon of comprehension and allow us to recover the legend of Asclepius and it’s cult with the different symbolic elements that structure it. The legend: The historic and mythological references about Asclepius’ existence gives structure to the legend in a real and not-real environment perduring in the occidental medicine tradition as a mystical reference to the deity for the medical practice. The cult: It’s based in the incubation and synthesizes healing rites and therapeutical practices, as medical as surgical; exercise, sleep cures and amusement activities. The symbol: The linguistic origin of Asclepius’ name, the symbolism of the legend protagonists and the iconographic representation of their attributes, converge in the Caduceus to represent the medical practices and ideas synthesis, all them related to the human life. Conclusion: Asclepius’ perception transcends the Olympic divinity and situates him as the healing archetype; that’s why Caduceus is consistent with the system-world representation that rules the actual medical practice.